Gastronomy, hospitality, and the future of the restaurant industry post-COVID-19 perspectives - Borges, Ana Pinto, 1980-; Almeida, Antonio Lopes de, 1966-; Vieira, Elvira, 1977-; Dias, Rui, 1970-; Rodrigues, Paula Cristina Lopes, 1970- (Business Science Reference, 2022)
"The main objective of the book is to contribute to the dissemination of knowledge, both to academics and professionals, in the areas of Gastronomy and Hospitality, and consequently Tourism, defining strategies and planning options"--